Utilization Pemanfaatan Ekstrak Kulit Ubi Jalar Ungu Sebagai Pengganti Crystal Violet pada Pewarnaan Gram - Andi Sri Nurul Hidayanti; Sulfiani Sulfiani; Nuramaniyah Taufiq (Poltekkes Kemenkes Padang, 2021)
Purple sweet potato has the high anthocyanin content. The anthocyanin content in purple sweet potato skin is higher than the anthocyanin in the tubers, namely 52.84-729.74 mg/100g while the tubers are 110.51 mg/100g. Natural dyes that have the potential to be extracted include anthocyanins. This research aimed to test anthocyanin dyes in purple sweet potato peel extract as the substitute for crystal violet in gram staining. The type of research used Quasi Experiments. This research was conducted in the Microbiology Laboratory of the Hasanuddin University Medical Faculty. In this research, extraction was carried out by using the solvent of Ethanol : Acetic Acid : Water (25: 1: 5). Furthermore, gram staining was carried out by using purple sweet potato peel extract using a concentration of 60%, 70%, 80%, 90%, 100% and crystal violet as positive control. The results of this research indicate that the staining used purple sweet potato peel extract concentrations of 60%, 70%, 80%, 90% in gram-positive Staphylococcus bacteria isolates showed poor bacterial staining results because the bacteria were not purple when compared to crystal violet dye. Where as at the concentration of 100% it showed good bacterial staining results because the bacteria was purple. Meanwhile, gram-negative e.coli bacteria isolates at the concentration of 60%, 70%, 80%, 90%, 100% showed good bacterial staining results because the bacteria were red. Suggestions for further research to do maceration longer.